strategic direction and its impact on institutional performance An exploratory study in the Directorate General of Curricula - خميس, لمى هادي (Journal of Economics and Administrative Sciences, 2025)
The objective of the research is to determine the nature of the strategic direction of the institution and its impact on enhancing the indicators of institutional performance. The strategic direction is the main purpose for which it was found. Therefore, it is the main engine for all activities and tasks that the institution can carry out to achieve its objectives within the environment in which it operates. The promotion of corporate performance indicators is one of the major challenges that senior management must address in order to help the organization invest its human resources in the best possible way.The research problem was determined by means of the intentional sample, consisting of (33) members of the administrative leadership in the Directorate above, The questionnaire was adopted as a tool for obtaining research data, which was prepared based on a number of ready-made measurements after being tested for honesty and consistency. The SPSS program was used to introduce and analyze research data, Statistical tools used in the analysis include: "percentage of frequency, mean, standard deviation, variance coefficient, Spearman correlation coefficient, and simple linear regression"The statistical tools resulted in a number of results, most of which confirmed the existence of a correlation relationship and a significant impact on the strategic direction in enhancing the indicators of institutional performance. Accordingly, the main hypotheses and sub-hypotheses included in the research were accepted. The researcher recommended that the research institution should identify the most important areas During which they promote institutional performance indicators and employ this when formulating a strategic direction.